2023
DOI: 10.1186/s13071-023-05928-5
|View full text |Cite
|
Sign up to set email alerts
|

The first report on Hepatozoon canis in dogs and wolves in Poland: clinical and epidemiological features

Katarzyna Tołkacz,
Milena Kretschmer,
Sabina Nowak
et al.

Abstract: Background Canine hepatozoonosis caused by Hepatozoon canis is a common infection in dogs, with frequent case reports from the Mediterranean region and more recently from several Central European countries, such as Hungary and Germany. Despite the high prevalence of H. canis in red foxes, no infections have been reported to date in dogs in Poland. We describe here the first autochthonous cases of H. canis infection in dogs, including their clinical features, and report the prevalence of H. cani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…gamonts in the blood of bears with high ESR and globulin values. Notably, changes in albumin, globulin, and ALP levels have also observed in other Babesia -infected hosts, such as camels ( Camelus dromedarius ) [ 53 ], dogs ( Canis familiaris ) [ 54 ], and cattle [ 55 ] as well as Hepatozoon -infected dogs [ 56 58 ]. Collectively, these hematological and plasma data may serve as a reference for future investigation on host and tick-borne pathogen relationships in wild bears.…”
Section: Discussionmentioning
confidence: 99%
“…gamonts in the blood of bears with high ESR and globulin values. Notably, changes in albumin, globulin, and ALP levels have also observed in other Babesia -infected hosts, such as camels ( Camelus dromedarius ) [ 53 ], dogs ( Canis familiaris ) [ 54 ], and cattle [ 55 ] as well as Hepatozoon -infected dogs [ 56 58 ]. Collectively, these hematological and plasma data may serve as a reference for future investigation on host and tick-borne pathogen relationships in wild bears.…”
Section: Discussionmentioning
confidence: 99%
“…So far, data on the occurrence of these diseases in dogs in Poland are fragmentary. The first cases of hepatozoonosis caused by Hepatozoon canis invasions in Poland were described in 2021–2022 ( 50 ). The infected dogs came to Poland from Ukraine (together with refugees) ( 9 ), but there were also dogs suffering from it which had never left Poland (autochthonous cases) ( 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…Poland is a country where vector-borne diseases such as babesiosis (caused by Babesia canis ), granulocytic anaplasmosis and Lyme disease are relatively frequently diagnosed in dogs ( 55 , 56 ). In recent years, isolated cases of infections with Babesia gibsoni ( 47 ), Hepatozoon canis ( 50 ), Leishmania infantum ( 18 , 41 ) and Dirofilaria immitis ( 29 ) have also been observed. This may be a consequence of the increased frequency of tourist trips with pet dogs to countries where these diseases occur.…”
Section: Introductionmentioning
confidence: 99%
“…However, it was shown that dogs naturally infected with H. canis showed no clinical signs of the parasite despite its presence being confirmed by PCR tests and cytology [15]. Furthermore, eosinophilia, leukocytosis, lymphocytosis, neutrophilia, and other hematological abnormalities were present in almost all dogs analyzed [17].…”
Section: Introductionmentioning
confidence: 98%